Early parenting: The roles of maltreatment, trauma symptoms, and future expectations. Issue 7 (23rd August 2014) - Thompson, Richard; Neilson, Elizabeth C.
ABSTRACT: The psychosocial determinants of early parenting are still not well understood. The current study used data on 115 girls in the Capella Project, who were followed longitudinally for the first 18 years of life. Potential predictors of early parenting assessed were child maltreatment, trauma symptoms, and girls' expectations for their socioeconomic outcomes. Cox regression survival analyses were conducted to predict time to the birth of first child. Significant unique predictors of early parenting included neglect, anxiety, low depression, and low expectations of going to college. Practice and research implications of these findings include the importance of neglect for risk of early parenting, the importance of ongoing trauma symptoms in youth, and the potentially protective influence of expectations of going to college.